Descripción etológica del gusano de la fruta del cultivo de naranjilla (Solanum quitoense) en laboratorio. Ceasa, sector Salache, provincia de Cotopaxi 2015 - Tipanluisa Aigaje, Anilsa Yolanda (2016)
This researching to describes the biology of worm farming fruit naranjilla (Solanum quitoense), has also made its way to determine the cycle life, habits and behavior, also the specimen of the pest is correctly identified in this study. The work was conducted at the farm of Mrs. Rosalia Aigaje farmer, land dedicated to the naranjilla grown for over 30 years, this is located in Napo province , El Chaco, Canton Santa Rosa Parish, testing it to implement average 20.2 average temperature 80 ° C, and relative humidity, 6% throughout the investigation. Thus determining the Neoleucinodes elegantalis presents four states, the cycle life lasts a total of 45.5 days, it presents behavior within five larval instarsit is nocturnal to leave the exsuvia to adulthood, as well as to take copulation activity, oviposition instantly and for food….